2017
DOI: 10.1186/s12889-017-4293-9
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti breeding ecology in Guerrero: cross-sectional study of mosquito breeding sites from the baseline for the Camino Verde trial in Mexico

Abstract: BackgroundUnderstanding the breeding patterns of Aedes aegypti in households and the factors associated with infestation are important for implementing vector control. The baseline survey of a cluster randomised controlled trial of community mobilisation for dengue prevention in Mexico and Nicaragua collected information about the containers that are the main breeding sites, identified possible actions to reduce breeding, and examined factors associated with household infestation. This paper describes findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
(27 reference statements)
0
17
0
2
Order By: Relevance
“…Five studies examined the occurrence and correlates of domiciliary and peri-domicilliary mosquito density, including sociodemographic characteristics, container types, and meteorological correlates [7377]. Specifically, Rodrigues et al [73] and Serpa et al [77] studied Aedes aegypti and Aedes albopictus , and Favaro et al [74], Morales-Pérez et al [75] and Schafrick et al [76] studied Aedes aegypti . Covered containers [7577], low education of the household head [75] and higher densities of residents per household [73] were found to be associated with higher risk of infestation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies examined the occurrence and correlates of domiciliary and peri-domicilliary mosquito density, including sociodemographic characteristics, container types, and meteorological correlates [7377]. Specifically, Rodrigues et al [73] and Serpa et al [77] studied Aedes aegypti and Aedes albopictus , and Favaro et al [74], Morales-Pérez et al [75] and Schafrick et al [76] studied Aedes aegypti . Covered containers [7577], low education of the household head [75] and higher densities of residents per household [73] were found to be associated with higher risk of infestation.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, Rodrigues et al [73] and Serpa et al [77] studied Aedes aegypti and Aedes albopictus , and Favaro et al [74], Morales-Pérez et al [75] and Schafrick et al [76] studied Aedes aegypti . Covered containers [7577], low education of the household head [75] and higher densities of residents per household [73] were found to be associated with higher risk of infestation. Two studies reported storm drain characteristics associated with mosquitoe presence: one related to Aedes aegypti and Culex quinquefasciatus presence [78], and the other to Aedes aegypti and Aedes albopictus [79].…”
Section: Resultsmentioning
confidence: 99%
“…Kelimpahan nyamuk telah memberikan dampak negatif yang signifikan terhadap kualitas hidup manusia di sekitarnya. 6 Selain itu habitatnya di pemukiman dan habitat stadium pradewasa pada bejana buatan yang berada di dalam ataupun di luar rumah. Faktor-faktor yang mempengaruhi perilaku Aedes aegypti meletakkan telurnya antara lain jenis dan warna penampungan air, airnya sendiri, suhu kelembaban, dan kondisi lingkungan setempat.…”
Section: Pendahuluanunclassified
“…The ecology of containers such as the presence of detritus in water, water temperature and surrounding habitat (type of vegetation) increases risk of mosquito infestation [ 21 , 30 32 ]. Human behavior and socio-demographic characteristics such as socio-economic status and water management methods further influence risk of infestation by Aedes immatures [ 16 , 29 , 30 , 33 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, determination of the risk of dengue, Zika, and chikungunya disease outbreaks in high risk regions has been based on larval surveillance and Stegomyia indices [14][15][16][17]. However, recent studies have shifted focus to include pupae in the surveillance of Aedes spp.…”
mentioning
confidence: 99%